Preparação, caracterização e estudos de liberação controlada de pancreatina encapsulada em diferentes hidrogéis - Olímpio, Fernanda Mendes De Paiva (2017)
Pancreatin (enzymatic complex composed of α-amylase, lipase and protease) is a biopharmaceutical used in the treatment of individuals who are deficient or insufficient in the production of pancreatic enzymes. The instability of these enzymes in the acidic medium can compromise their activities, reducing the effectiveness of the treatments performed. In an attempt to preserve enzymatic activities and to provide a delayed release of pancreatin, natural polymer hydrogels were prepared to act as vehicles for pancreatin which was encapsulated into their polymer matrices. The obtained hydrogels were characterized through infrared spectroscopy, thermogravimetric analysis, encapsulation efficiency, swelling degree and swelling profile. In addition, release studies of encapsulated pancreatin in the hydrogels and released from a commercially available formulation, Creon®, were performed. In general, all hydrogels had a low swelling degree when submitted to simulated gastric fluid and high swelling degree and complete solubilization of the polymer matrice, promoting the enzymes release in simulated intestinal fluid. Among the three hydrogels prepared and analyzed, the alginate hydrogel was distinguished by its higher encapsulation efficiency and enzymes release at pH similar to the action site, so it was used for comparison with the results obtained by Creon®, in the pancreatin release studies. This comparison showed that the enzymatic release by the alginate hydrogel was faster and more complete, whereas the Creon® coated minimichrospheres that did not dissolve until the end of the analyzes.